Media Informasi Pekerjaan Paruh Waktu Secara Online - Moch Anwar Syafii; Noven Indra Prasetya; Emmy Wahyuningtyas (Melek IT : Information Technology Journal, 2016)
The development of Internet technology society increasingly facilitated in conducting several processes, one satu contohnya labor penenerimaan online. Information needs work, especially information on job opportunities through information media is increasing. But today most job openings must be a permanent employee or perkeja must do their work in companies that provide jobs. In the existing problems the author makes a media job information onlin e. In the problem will be repaired and enhancing existing features on the website freelancer.com. The first fix the tax system, before taxes cut by 10%. In this issue the more wages given the more taxes are obtained. In order not to tax a lot of it will be in charge of tax price of each work is 50ribu rupiah. The problems that the two give a rating and comment features that job seekers and job providers believe provides jobs and complete the work by looking more ratings and comments whatever is in the profile. Additional features for additional advertising revenue cost of website and other web feature additions fire for a job search in any other website. Results of improvements and additions to existing features on the website freelancer.com will facilitate users in understanding the job search system and installation work, Making job seekers believe the work deals with seeing the ratings feature is added, and facilitate interaction between users using the chat feature.